Hygiene compliance in Moroccan mass catering establishments: A cross-sectional assessment - Friki, Firdaous; Chamlal, Hamid; Barakat, Imane; Belaoufi, Halima; Moustakim, Rachida; El Habazi, Abdellah; Fassouane, Abdelaziz; Belahsen, Rekia (Hasanuddin University Food Science and Technology Study Program, 2025)
With meals prepared outside the home posing a higher risk of foodborne outbreaks, the growing trend towards eating out raises concerns about the quality of meals served in mass catering establishments (MCEs). This study aimed to assess the determinants of hygiene in MCEs and identify the factors with the highest levels of non-compliance. A cross-sectional descriptive survey was conducted in six MCEs. Data on kitchen managers and food preparation workers (FPWs) were collected using a questionnaire. Data on hygiene status were collected through observations during food preparation and interviews with establishment managers and FPWs. Hygiene status was assessed using the method recommended by the Moroccan Ministry of Health for the inspection of food establishments. The result showed that 67% of the establishments outsource the management of their canteens. No establishment has a HACCP plan. 88% of FPWs were women. Among them 28% have never been to school, and the majority (88%) have never received any hygiene training. Two thirds of the establishments have a compliance rate of over 50% with 63% as the highest rate and the lowest compliance rate of 30%. Regarding the compliance rates according to the 5 dimensions assessed, the highest rates are obtained for Environment and Raw Material dimensions. However, Method and Labor dimensions have recorded the highest non-compliance rates. This study highlights the urgent need to enhance food handlers' knowledge of good hygiene practices and recommends implementing the HACCP system to ensure food safety in MCEs.